Analisis Keputusan Konsumen Berbelanja di Toko UD. Winmart Singaraja - I Gusti Made Oka Astana; I Made Panji Dwipayana (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
This research was conducted at the UD. Winmart Singaraja store to determine the effect of product completeness, product layout, price, and location in consumer decisions to do shopping. The approach in this study uses a quantitative approach, where the data collection technique used in this study is a questionnaire with a rating scale measurement of 1-10, and the respondents are consumers from UD. Winmart Singaraja stores as many as 100 people. In this study, the data analysis technique used is the Multiple Linear Regression Model with the help of the SPSS Statistics application. The results obtained indicate that each independent variable used in this study has a positive and significant influence on purchasing decisions at UD. Winmart Singaraja Stores.